New species of Orthosia Decne. (Apocynaceae-Asclepiadoideae) from Paraná, and a key to the species of southern Brazil - Pereira, Jorge Fontella-; de Goes, Monique Britto (Revista de Biologia Neotropical / Journal of Neotropical Biology, 2017)
Ver resumo em pdf no artigo